Silver / gold and silver core-shell quantum dot and preparation method thereof
By preparing silver/gold-silver core-shell quantum dots, the strong coupling effect and electronegativity characteristics of their core-shell structures are used to solve the problem of insufficient sensitivity and selectivity in Cu2+ detection, and efficient fluorescence detection is achieved, with high sensitivity and high selectivity.
Patent Information
- Application Number
- CN202411594788.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-10
- Publication Date
- 2025-02-25
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quantum dot luminescent materials, and in particular relates to a silver / gold-silver core-shell quantum dot and a preparation method thereof. Background Art
[0002] Copper ion (Cu 2+ ) is an essential trace element in all biological systems and plays a vital role in various physiological processes. The average blood copper concentration of the normal group is 15.7-23.6 μM. Excessive Cu 2+ It is highly toxic to organisms, causing gastrointestinal and cellular homeostasis disorders, leading to severe neurodegenerative diseases. 2+ Environmental contamination caused by Cu is still a major problem. The US Environmental Protection Agency has set the permissible limit in drinking water at 20 μM. 2+ Real-time and highly accurate evaluation of activity is crucial for clinical diagnosis and environmental protection. 2+ There are many techniques for the determination of Cu, such as electrochemistry, fluorescence, and surface-enhanced Raman scattering. Among these strategies, fluorescence analysis stands out due to its high sensitivity and ease of operation. Although significant progress has been made, it is still difficult to construct a Cu 2+ Fluorometric assays with high sensitivity, high selectivity, and low sample consumption are still highly desirable.
[0003] Fluorescence technology has penetrated into many fields of chemistry, physics, and biological sciences, such as heavy metal detection, optical communication, and bioimaging. Among the many fluorescent materials, metal quantum dots, especially gold and silver quantum dots, have attracted widespread attention due to their fascinating optical properties, excellent biocompatibility, and outstanding catalytic activity. However, the limited quantum yield and fluorescence intensity of gold and silver quantum dots restrict their applications. Therefore, in recent years, improving the fluorescence properties of metal quantum dots has become a prominent research area. Generally, there are two main sources of fluorescence: 1) intrinsic quantum effects; 2) interactions between metal cores and surface ligands. While electron concentration can significantly affect the fluorescence intensity of gold and silver quantum dots, enriching electrons to gold and silver quantum dots or accelerating the transfer of electrons from ligands to gold and silver quantum dots can significantly improve the quantum yield and fluorescence intensity of metal quantum dots. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing silver / gold-silver core-shell quantum dots. The silver / gold-silver core-shell quantum dots prepared by the method have excellent properties such as stable structure, high temperature resistance, high surface plasmon fluorescence enhancement, sensitive and fast heavy metal detection, etc., which has important reference significance for the construction of high-performance luminescent materials.
[0005] A second object of the present invention is to provide a silver / gold-silver core-shell quantum dot.
[0006] In order to achieve one of the above purposes, the present invention adopts the following technical solutions:
[0007] A method for preparing silver / gold-silver core-shell quantum dots, the preparation method comprising the following steps:
[0008] Step S1, at a temperature of 20 to 25° C., adding a silver nitrate solution with a molar concentration of 20 to 30 mmol / L and a sodium hydroxide solution with a molar concentration of 0.9 to 1.1 mol / L to a methylthiouracil solution with a molar concentration of 8 to 10 mmol / L, sequentially performing magnetic stirring, ultrafiltration centrifugal filtration and washing, and then dispersing the solution into the 8 to 10 mmol / L methylthiouracil solution to obtain an inner core solution of silver nanospheres;
[0009] Step S2, at a temperature of 20 to 25° C., adding a silver nitrate solution with a molar concentration of 20 to 30 mmol / L, a sodium hydroxide solution with a molar concentration of 0.9 to 1.1 mol / L, and chloroauric acid with a molar concentration of 20 to 30 mmol / L to the inner core solution of the silver nanospheres, and magnetically stirring for 3.8 to 4.2 hours to obtain a silver / gold-silver core-shell quantum dot solution;
[0010] Step S3, at a temperature of 1 to 6° C., continuously introducing air into the silver / gold-silver core-shell quantum dot solution for 4 to 8 hours to obtain silver / gold-silver core-shell quantum dots.
[0011] Furthermore, in the step S1, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the methylthiouracil solution and the methylthiouracil solution used for dispersion is 1.07-5.71:1:31.25:31.25.
[0012] Furthermore, in the step S1, the magnetic stirring rate is 760-830 rpm / min, and the time is 1.7-2.2 hours.
[0013] Furthermore, in the step S1, an ultrafiltration centrifuge tube with a molecular weight of 10KDa is used for ultrafiltration centrifugal filtration, the rotation speed of the ultrafiltration centrifugal filtration is 6300-6700rpm, and the ultrafiltration centrifugal filtration is performed for 25-35 minutes.
[0014] Furthermore, in the step S1, the washing is performed 3 to 4 times.
[0015] Furthermore, in step S2, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the chloroauric acid solution and the silver nanosphere inner core solution is 1.07-5.71:1:1.07-5.71:31.25.
[0016] Furthermore, in the step S2, the rate of the magnetic stirring is 760-830 rpm / min.
[0017] In order to achieve the second objective above, the present invention adopts the following technical solution:
[0018] A silver / gold-silver core-shell quantum dot for copper ion fluorescence detection, comprising a silver core and a gold-silver quantum dot shell wrapped outside the silver core.
[0019] The silver / gold-silver core-shell quantum dots for copper ion fluorescence detection in the present invention are prepared by the above-mentioned preparation method.
[0020] The invention uses silver balls as cores and gold-silver quantum dots as shells, and utilizes the electronegativity between gold and gold and silver to induce the transfer of silver core electrons into the gold-silver shells, thereby improving the fluorescence intensity and quantum yield thereof; utilizes the plasmon effect generated by the strong coupling between the silver core and the gold-silver shells to promote the transfer of surface ligand electrons into the gold-silver shells, thereby improving the fluorescence intensity and quantum yield thereof; and increases the positive charge of the shell layer by introducing air for oxidation, further inducing electron transfer, thereby improving the fluorescence intensity and quantum yield thereof.
[0021] In summary, the technical solution of the present invention has the following technical effects:
[0022] The present invention promotes the transfer of ligand electrons on the surface of methylthiouracil into the gold-silver shell by utilizing the plasmon effect generated by the strong coupling between the silver core and the gold-silver shell and the electronegativity between gold and silver, thereby improving the fluorescence intensity and quantum yield thereof; and improves the positive charge of the gold-silver shell layer by utilizing the oxidation effect of air, thereby further inducing electron transfer and improving the fluorescence intensity and quantum yield thereof.
[0023] The silver / gold-silver core-shell quantum dots of the present invention have a fluorescence intensity 94 times higher than that of gold-silver alloy quantum dots, a quantum yield 32 times higher, and are resistant to high temperatures of 90 degrees. 2+ It has high sensitivity and selectivity. Its high quantum yield and fluorescence intensity are beneficial to the concentration judgment of copper ion fluorescence measurement, which can realize the determination of Cu 2+ Simple and fast ultra-sensitive detection, with a detection concentration range of 1 to 173 μM / L and a correlation coefficient of 98.85%, which can be used for the detection of heavy metal copper;
[0024] The silver / gold-silver core-shell quantum dots of the present invention have excellent properties such as stable structure, high temperature resistance, high surface plasmon fluorescence enhancement, sensitive and fast heavy metal detection, etc., and have important reference significance for the construction of high-performance luminescent materials.
[0025] The present invention adopts the hydrothermal method to construct an atomic-level core-shell structure at the nanoscale, and obtains a good confinement effect. The normal temperature and pressure method is simple and easy to operate, which provides a certain reference for the synthesis of high-performance luminescent materials and biological detection materials. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] Step S1, at a temperature of 22° C., a silver nitrate solution with a molar concentration of 30 mmol / L and a sodium hydroxide solution with a molar concentration of 0.9 mol / L are added to a methylthiouracil solution with a molar concentration of 10 mmol / L, and then magnetically stirred at a rate of 760 rpm / min for 2.2 hours, and then ultrafiltered and centrifuged at a speed of 6300 rpm using an ultrafiltration centrifuge tube with a molecular weight of 10 KDa for 35 minutes, and then washed three times and dispersed into a 10 mmol / L methylthiouracil solution to obtain an inner core solution of silver nanospheres.
[0029] Among them, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the methylthiouracil solution and the methylthiouracil solution used for dispersion is 5.71:1:31.25:31.25.
[0030] Step S2, at a temperature of 22° C., a silver nitrate solution with a molar concentration of 30 mmol / L, a sodium hydroxide solution with a molar concentration of 0.9 mol / L, and a chloroauric acid solution with a molar concentration of 30 mmol / L are added to the inner core solution of the silver nanospheres, and then magnetically stirred at a rate of 830 rpm / min for 4.2 hours to obtain a silver / gold-silver core-shell quantum dot solution.
[0031] Among them, the volume ratio of silver nitrate solution, sodium hydroxide solution, chloroauric acid solution and silver nanosphere inner core solution is 5.71:1:5.71:31.25.
[0032] Step S3, at a temperature of 6° C., continuously introducing air into the silver / gold-silver core-shell quantum dot solution for 8 hours to obtain silver / gold-silver core-shell quantum dots, and storing them at 1-6° C.
[0033] Embodiment 2:
[0034] Step S1, at a temperature of 20° C., a silver nitrate solution with a molar concentration of 20 mmol / L and a sodium hydroxide solution with a molar concentration of 1.1 mol / L are added to a methylthiouracil solution with a molar concentration of 8 mmol / L, and then magnetically stirred at a rate of 830 rpm / min for 1.7 hours, and then ultrafiltered and centrifuged at a speed of 6300 rpm using an ultrafiltration centrifuge tube with a molecular weight of 10 KDa for 25 minutes, and then washed 4 times and dispersed into an 8 mmol / L methylthiouracil solution to obtain an inner core solution of silver nanospheres.
[0035] Among them, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the methylthiouracil solution and the methylthiouracil solution used for dispersion is 1.07:1:31.25:31.25.
[0036] Step S2, at a temperature of 20° C., adding a silver nitrate solution with a molar concentration of 20 mmol / L, a sodium hydroxide solution with a molar concentration of 1.1 mol / L, and a chloroauric acid solution with a molar concentration of 20 mmol / L to the inner core solution of the silver nanospheres, and then magnetically stirring at a rate of 760 rpm / min for 3.8 hours to obtain a silver / gold-silver core-shell quantum dot solution.
[0037] Among them, the volume ratio of silver nitrate solution, sodium hydroxide solution, chloroauric acid solution and silver nanosphere inner core solution is 1.07:1:1.07:31.25.
[0038] Step S3, at a temperature of 1° C., continuously introducing air into the silver / gold-silver core-shell quantum dot solution for 4 hours to obtain silver / gold-silver core-shell quantum dots, and storing them at 1-6° C.
[0039] Embodiment 3:
[0040] Step S1, at a temperature of 25° C., a silver nitrate solution with a molar concentration of 25 mmol / L and a sodium hydroxide solution with a molar concentration of 1.0 mol / L are added to a methylthiouracil solution with a molar concentration of 9 mmol / L, and then magnetically stirred at a rate of 800 rpm / min for 2 hours, and then ultrafiltered and centrifuged at a speed of 6300 rpm using an ultrafiltration centrifuge tube with a molecular weight of 10 KDa for 30 minutes, and then washed 4 times and dispersed into a 9 mmol / L methylthiouracil solution to obtain an inner core solution of silver nanospheres.
[0041] Among them, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the methylthiouracil solution and the methylthiouracil solution used for dispersion is 2.14:1:31.25:31.25.
[0042] Step S2, at a temperature of 25° C., a silver nitrate solution with a molar concentration of 25 mmol / L, a sodium hydroxide solution with a molar concentration of 1.0 mol / L, and a chloroauric acid solution with a molar concentration of 25 mmol / L are added to the inner core solution of the silver nanospheres, and then magnetically stirred at a rate of 800 rpm / min for 4 hours to obtain a silver / gold-silver core-shell quantum dot solution.
[0043] Among them, the volume ratio of silver nitrate solution, sodium hydroxide solution, chloroauric acid solution and silver nanosphere inner core solution is 2.14:1:2.14:31.25.
[0044] Step S3, at a temperature of 5° C., continuously introducing air into the silver / gold-silver core-shell quantum dot solution for 6 hours to obtain silver / gold-silver core-shell quantum dots, and storing them at 1-6° C.
[0045] Comparative Example 1:
[0046] At a temperature of 25°C, a silver nitrate solution with a molar concentration of 25 mmol / L, a sodium hydroxide solution with a molar concentration of 1.0 mol / L, and a chloroauric acid solution with a molar concentration of 25 mmol / L were added to a methylthiouracil solution with a molar concentration of 9 mmol / L, and then magnetically stirred at a rate of 800 rpm / min for 4 hours to obtain gold-silver alloy quantum dots. The volume ratio of the silver nitrate solution, the sodium hydroxide solution, the chloroauric acid solution, and the methylthiouracil solution was 1.43:1:4.29:31.25.
[0047] The particle size of the silver spheres in Examples 1 to 3 is 4.0 to 4.2 nm, and the particle size of the silver / gold-silver core-shell quantum dots is 6.0 to 6.3 nm. The gold-silver shell tightly wraps the silver core. The infrared spectra at 1593 and 1521 cm -1 The peak at 1121 cm is attributed to the stretching of the C=O and N–H bands located in the pyrimidine ring of the surface ligand 5-MTU. -1 The peaks are attributed to alkyl carbon, and the stretching vibrations of C=O, N–H, and C=N are concentrated at 1632, 1520, and 1441 cm – 1 .
[0048] The silver / gold-silver core-shell quantum dots of Examples 1 to 3 above generate a plasmon peak at 433 nm, with a light emission wavelength of 493 nm and a full width at half maximum of 71 nm.
[0049] The excitation peaks of the gold-silver alloy quantum dots of Examples 1 to 3 are located at 401 nm. In addition to the excitation peak at 401 nm, the silver / gold-silver core-shell quantum dots exhibit two new excitation modes at 375 nm and 433 nm.
[0050] The fluorescence obtained by the silver / gold-silver core-shell quantum dots of the above-mentioned embodiments 1 to 3 when excited at 433nm is 15.88 times higher than that of the gold-silver alloy quantum dots of comparative example 1, and the quantum yield is 2.6 times higher. When the positive charge is enhanced, the fluorescence obtained by the silver / gold-silver core-shell quantum dots when excited at 433nm is 94 times higher than that of the gold-silver alloy quantum dots of comparative example 1, and the quantum yield is 32 times higher. The fluorescence lifetime is 12 times that of the gold-silver alloy quantum dots of comparative example 1. The silver / gold-silver core-shell quantum dots of the above-mentioned embodiments 1 to 3 can linearly measure the concentration of copper ions.
[0051] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing silver / gold-silver core-shell quantum dots, characterized in that: The preparation method comprises the following steps: Step S1, at a temperature of 20 to 25° C., adding a silver nitrate solution with a molar concentration of 20 to 30 mmol / L and a sodium hydroxide solution with a molar concentration of 0.9 to 1.1 mol / L to a methylthiouracil solution with a molar concentration of 8 to 10 mmol / L, sequentially performing magnetic stirring, ultrafiltration centrifugal filtration and washing, and then dispersing the solution into the 8 to 10 mmol / L methylthiouracil solution to obtain an inner core solution of silver nanospheres; Step S2, at a temperature of 20 to 25° C., adding a silver nitrate solution with a molar concentration of 20 to 30 mmol / L, a sodium hydroxide solution with a molar concentration of 0.9 to 1.1 mol / L, and chloroauric acid with a molar concentration of 20 to 30 mmol / L to the inner core solution of the silver nanospheres, and magnetically stirring for 3.8 to 4.2 hours to obtain a silver / gold-silver core-shell quantum dot solution; Step S3, at a temperature of 1 to 6° C., continuously introducing air into the silver / gold-silver core-shell quantum dot solution for 4 to 8 hours to obtain silver / gold-silver core-shell quantum dots.
2. The preparation method according to claim 1, characterized in that: In the step S1, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the methylthiouracil solution and the methylthiouracil solution used for dispersion is 1.07-5.71:1:31.25:31.
25.
3. The preparation method according to claim 2, characterized in that: In the step S1, the magnetic stirring rate is 760-830 rpm / min, and the time is 1.7-2.2 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S1, an ultrafiltration centrifuge tube with a molecular weight of 10KDa is used for ultrafiltration centrifugal filtration, the rotation speed of the ultrafiltration centrifugal filtration is 6300-6700rpm, and the ultrafiltration centrifugal filtration is performed for 25-35 minutes.
5. The preparation method according to claim 4, characterized in that: In the step S1, the washing is performed 3 to 4 times.
6. The preparation method according to claim 5, characterized in that: In step S2, the volume ratio of the silver nitrate solution, the sodium hydroxide solution, the chloroauric acid solution and the silver nanosphere inner core solution is 1.07-5.71:1:1.07-5.71:31.
25.
7. The preparation method according to claim 6, characterized in that: In the step S2, the rate of the magnetic stirring is 760-830 rpm / min.
8. A silver / gold-silver core-shell quantum dot for copper ion fluorescence detection, characterized in that: The silver / gold-silver core-shell quantum dots include a silver core and a gold-silver quantum dot shell wrapped outside the silver core.